Spontaneous malignant glaucoma in a patient with patent peripheral iridotomy - Premsenthil, Mallika (BioMed Central, 2012)
BACKGROUND: To report a case of spontaneous malignant glaucoma in an Asian female. To propose the term “positive vitreous pressure glaucoma” to reflect the pathophysiology, treatment and prognosis of the condition. CASE PRESENTATION: A 56-year old Chinese female was diagnosed of primary angle closure glaucoma and had bilateral laser peripheral iridotomy one year ago. She presented with spontaneous onset of malignant glaucoma involving the left eye. The condition was treated successfully; the final best corrected visual acuity was 0.67 (decimal notation). CONCLUSION: This case highlights that acute angle closure attack can occur in an eye with patent peripheral iridotomy. Early recognition and treatment is essential for good visual prognosis.